PENGARUH GAJI, BONUS DAN FASILITAS TERHADAP MOTIVASI KERJA KARYAWAN (Studi Pada PT. BRI Unit I Sumbawa Besar) - I Ismawati; Intan Komalasari (Fakultas Ekonomi dan Manajemen, 2022)
The purpose of this study was to determine the effect of salary (X1), bonus (X2), and facilities (X3) on employee work motivation (Y) at Bank Rakyat Indonesia Tbk Unit Kota 1 Sumbawa Besar, either partially or simultaneously. This type of research is associative research. The data used is primary data in the form of respondents' answers obtained through questionnaires. The population in this study were all employees of PT. Bank Rakyat Indonesia (BRI) Unit 1 Sumbawa Besar, totaling 20 people. The number of employees can be known with certainty and the number is not large, so the determination of the number of samples is carried out using a saturated sample. The data analysis technique used multiple linear regression analysis, t and F statistical tests, and the coefficient of determination (R2) test. The test was carried out using the SPSS version 16.0 application for windows. The research findings show that bonuses and facilities partially have a positive and significant effect on employee work motivation, while salaries partially have no effect on employee work motivation at Bank Rakyat Indonesia (BRI) Unit 1 Sumbawa Besar. Simultaneously, salaries, bonuses and facilities have a significant effect on employee motivation at Bank Rakyat Indonesia (BRI) Unit 1 Sumbawa Besar. The ability of the salary, bonus and facilities variables in influencing variations in employee motivation changes at Bank Rakyat Indonesia (BRI) Unit 1 Sumbawa Besar is 71.7% or is at a high level of correlation (relationship) so that the relationship is significant (meaningful), while the rest is 28.3% influenced by other variables outside the study.